-2x+5+8x=-1+6+6x

Simple and best practice solution for -2x+5+8x=-1+6+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+5+8x=-1+6+6x equation:


Simplifying
-2x + 5 + 8x = -1 + 6 + 6x

Reorder the terms:
5 + -2x + 8x = -1 + 6 + 6x

Combine like terms: -2x + 8x = 6x
5 + 6x = -1 + 6 + 6x

Combine like terms: -1 + 6 = 5
5 + 6x = 5 + 6x

Add '-5' to each side of the equation.
5 + -5 + 6x = 5 + -5 + 6x

Combine like terms: 5 + -5 = 0
0 + 6x = 5 + -5 + 6x
6x = 5 + -5 + 6x

Combine like terms: 5 + -5 = 0
6x = 0 + 6x
6x = 6x

Add '-6x' to each side of the equation.
6x + -6x = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| (3)/(4x)=(6)/x=1 | | 7x-3=2*(x+6) | | 7x-5x+4x= | | 8+8x=22 | | 7x-3[4x+8]=11 | | sin(15)=5/x | | 0=80x-16x^2 | | 2*(-3a+5)=-4*(a+4) | | 9.3x+(8.5x)= | | logx=-67 | | 3t^3-t^2+t+2t^2=0 | | y^2=2cx+c^2 | | 9-6=38/2 | | -3*(y+3)=2y+3 | | 60-5y=10 | | 4/3*3.14*36599.0697^3 | | 9x-12y+16=34 | | 0=2x(x+1)-2 | | 3w-4+10=5w-6+2w | | 16p^2-8p+c=0 | | 4/3*3.14*18^3 | | (128x^20z^17)^1/5 | | 203=-5(1+6b)-2 | | 4/3*3.14*25^3 | | 7=1/3b | | 1x+-9=8+5 | | P-2.5=12.55 | | 4/3*3.14*22^3 | | (-3,5);y=1/3x-2 | | (2x+5)-(5x+4)=-2(x-3)+6 | | (6x^9)(3x^8)= | | 6w+10-3w=10+5w+4 |

Equations solver categories